Vesicular glutamate transport at a central synapse limits the acuity of visual perception in zebrafish - Smear, Matthew C. (2007)
Visual acuity is constrained by the function and distribution of synapses in the visual pathway, but the limiting factors have not been experimentally identified. We show here that zebrafish blumenkohl (blu) mutants are impaired in resolving rapid movements and fine spatial detail in their visual environment. The blu gene encodes a vesicular glutamate transporter expressed by retinal ganglion cells. Mutant retinotectal synapses release less glutamate, per vesicle and per terminal, and are depressed more quickly in response to high-frequency stimulation. The kinetics of this synaptic fatigue match the observed reduction in temporal sensitivity. In addition, mutant axons arborize more extensively, thus increasing the number of synaptic terminals and effectively normalizing the combined input to postsynaptic cells in the tectum. This presumably homeostatic response results in larger receptive fields of tectal cells and a degradation of the retinotopic map. As predicted, mutants have a selective deficit in the capture of small prey objects, a behavior dependent on the tectum. Our studies have linked the disruption of a synaptic protein to complex changes in neural circuitry and behavior.